Pengaruh Olahraga Terhadap Coronavirus Disease 2019 - Apituley, Tracy L. D; Pangemanan, Damajanty H. C.; Sapulete, Ivonny M. (Jurnal Biomedik : JBM, 2021)
Abstract: Coronavirus disease 2019 (COVID-19) is a disease that attacks the respiratory tract. COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 cases in the world and Indonesia continue to increase, and people are urged to do activities at home. COVID-19 caused a decrease in physical activity in society which can cause people to spend more time on cell phones, have irregular sleep patterns, and gain weight. Lack of physical activity has an impact on decreasing immune system, making it susceptible to infection with COVID-19. Research shows that exercise can reduce the risk of disease. This literature review aims to determine the effect of exercise on the 2019 coronavirus disease. The research method used is in the form of a literature review with data searches using three databases, which is Pubmed, Google Scholar, and ClinicalKey. The keywords used were Sport OR Physical Activity OR Exercise AND COVID-19 OR Coronavirus 2019. After being selected based on inclusion and exclusion criteria, there were 12 journal article reviews that would be reviewed. The results showed exercise can improve the immune system, metabolic health, mental health, muscle strength and cardiovascular function. The benefits of exercise are obtained if you do moderate intensity exercise regularly. In general, the recommended sports are aerobic and anaerobic exercises that can be done at home. In conclusion, exercise has a good effect on COVID-19.Keywords: Sports, Coronavirus disease 2019 (COVID-19)Â Â Abstrak: Coronavirus disease 2019 (COVID-19) merupakan penyakit yang menyerang saluran pernapasan. COVID-19 disebabkan oleh severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Kasus COVID-19 di dunia dan Indonesia terus meningkat sehingga dihimbaukan kepada masyarakat untuk melakukan aktivitas di rumah saja. COVID-19 mengakibatkan penurunan aktivitas fisik pada masyarakat yang dapat menyebabkan lebih banyak menghabiskan waktu di handphone, memiliki pola tidur tidak teratur, dan terjadi peningkatan berat badan. Kurang melakukan aktivitas fisik berdampak terhadap penurunan daya tahan tubuh sehingga rentan terinfeksi COVID-19. Penelitian-penelitian menunjukkan olahraga mampu menurunkan risiko penyakit. Tinjauan pustaka ini bertujuan untuk mengetahui pengaruh olahraga terhadap coronavirus disease 2019. Metode penelitian yang digunakan dalam bentuk literature review dengan pencarian data menggunakan tiga database yaitu Pubmed, Google Scholar, dan ClinicalKey. Kata kunci yang digunakan yaitu Sport OR Physical Activity OR Exercise AND COVID-19 OR Coronavirus 2019. Setelah diseleksi berdasarkan kriteria inklusi dan eksklusi didapatkan 12 jurnal article review yang akan dilakukan review. Hasil dari literature review didapatkan olahraga mampu meningkatkan sistem imunitas, kesehatan metabolik, kesehatan mental, kekuatan otot dan fungsi kardiovaskular. Manfaat olahraga diperoleh jika melakukan olahraga intensitas sedang dengan teratur. Secara umum olahraga yang disarankan yaitu olahraga aerobik dan anaerobik yang dapat dilakukan dirumah. Sebagai simpulan, olahraga memberi pengaruh yang baik terhadap COVID-19.Kata Kunci: Olahraga, Coronavirus disease 2019 (COVID-19)